Electromagnetic ion-cyclotron waves occurrence on the Van Allen radiation belts using the Van Allen Probes mission dataset - Claudia Medeiros (2020)
Energetic charged particles trapped in Earths magnetic field lines constitute the so-called Van Allen radiation belts. The inner most radiation belt is more stable, whereas the outer radiation belt is more dynamic. Plasma waves can propagate either along or across geomagnetic field lines and they can interact with charged particles thereby changing the radiation belt configuration. Among such waves the electromagnetic ion cyclotron (EMIC) waves, are of special interest in this work, since they are responsible for pitch angle-scattering relativistic electrons into the loss cone. Both pitch angle-resolved electron fluxes data and high time-resolution magnetic field measurements acquired from the twin, identically instrumented NASAs Van Allen Probes mission are used here, and they span a time interval of more than 4 years. The focus is to investigate the spatial distribution and the occurrence rate of EMIC waves in the outer Van Allen radiation belt during this period as well as the possible role played by EMIC waves in the reconfiguration of an electron butterfly pitch angle distribution (PAD) shape that resulted in an unusual electron butterfly PAD shape. A case study (MEDEIROS et al., 2019) revealed the likely association between EMIC waves occurrence and such unusual electron butterfly PAD. Then, two machine learning-based techniques have been employed with the first of them, referred to as Bag-of-Features (BoF, Medeiros et al. (2020)), being responsible to find, in a semi-automated way, EMIC wave events in a 4-year span dataset of magnetic field spectrogram images, and the second algorithm, known as Self Organizing Map (SOM, Souza et al. (2016)), would find unusual electron butterfly PAD shapes.By matching both the EMIC waves and the unusual electron butterfly PAD shape surveys the following conclusions are found: (1) the BoF technique performed nearly as good as the visual classification method with the enormous advantage that the BoF technique greatly expedites the analysis by accomplishing the task in just a few minutes; (2) for the period of one full Van Allen Probes orbit precession the unusual electron butterfly PAD shape found by Medeiros et al. (2019) is indeed unusual when considering events wherein there is at least a 10 minutes persistence. These events correspond to only 0.3% of the whole 1.8 MeV energy electron PADs dataset used for the same interval; (3) persistent unusual electron butterfly PAD events generally occur throughout the nightside region, at L-shell locations larger than about 5RE, with a slightly higher occurrence rate in the 01:0002:00 MLT range; (4) visual inspection of a small subset, that is, 23 events, containing persistent unusual electron butterfly PAD shapes show that they are indeed associated with EMIC waves occurrence for 22 events; (5) it is argued that EMIC waves can be the dominant factor in the relativistic electron flux reduction at pitch angles < 45 and > 135 which in turn lead to the appearance of such unusual electron butterfly PAD shapes.